STAGES OF THE ALL-AXIOLOGICAL FORMATION OF THE NATIONAL VALUE SYSTEM - Kdirbayev Qonisbay Muratbay Uli (American Journal Of Social Sciences And Humanity Research, 2023)
This article described the stages of the all-axiological formation of the national value system. The specifics of each period were analyzed.